PENINGKATAN MUTU KINERJA KARYAWAN DILIHAT DARI KOMUNIKASI INTERPERSONAL DAN TEAM WORK MELALUI EFIKASI DIRI SEBAGAI VARIABEL INTERVENING PUSAT PENELITIAN KELAPA SAWIT MEDAN - Aswin Muhammad Ginting; Ezzah Nahrisah; Arasy Ayu Setiamy (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This study aims to determine interpersonal communication and team work on employee performance mediated by self-efficacy on PPKS Medan employees. The total population in this study amounted to 135 people, using the saturated sample technique, the total number of PPKS Medan employees was obtained. The analysis technique used is quantitative. Sources of data in this study using primary data. While the type of research used in this study is associative with a quantitative approach, the method used in this research is statistics with data collection techniques through questionnaires to all PPKS Medan employees. The results showed that interpersonal communication had a significant positive effect on employee performance (tcount 3,009 and significance 0.000 <0.05) for PPKS Medan employees. Team work has a positive and significant effect on employee performance (tcount 2.473 and significance 0.000 <0.05) PPKS Medan employees. Self-efficacy has a positive and significant effect on employee performance (tcount 4.481 and significance 0.000 <0.05) PPKS Medan employees, Interpersonal communication has a positive and significant effect on self-efficacy (tcount 3.120 and significance 0.000 <0.05) PPKS Medan employees, Team work positive and significant effect on self-efficacy (ttable 1.656 and significance 0.000 <0.05) PPKS Medan employees